Derivational Suffixes in Speech Entitled “I Have A Dream” By Martin Luther King Jr - Adriana Natalia Malo; Ida Bagus Gde Nova Winarta (Universitas Islam Negeri Palopo, 2025)
The aim of this study is to analyze the use of derivational suffixes in Martin Luther King Jr.’s speech titled “I Have a Dream.” A total of 42 instances of derivational suffixes were identified in the speech. This research applies Katamba’s (1993) morphological theory within a qualitative descriptive analysis framework to examine how suffixation alters word classes and enhances rhetorical impact. The analysis shows that noun derived from verb derivation is the most productive process (64.3% of cases), reflecting the rhetorical function of abstracting actions into powerful ideological concepts. Derivational suffixes are used extensively to strengthen emotional appeal, convey abstract ideals, and reinforce persuasive messages. Words formed through suffixation contribute to the speech’s stylistic depth and ideological clarity, particularly in themes of justice, equality, and freedom. The findings highlight the significant role of derivational morphology in shaping persuasive political discourse and suggest practical implications for discourse analysis and English language teaching.